Peran Kepuasan Nasabah dalam Memediasi Pengaruh Kualitas Layanan dan Kepercayaan terhadap Loyalitas Nasabah PT Mega Central Finance (MCF) Cabang Garut - Ramadhani, Novia; Susilawati, Wati (Jurnal Ekonomi, Bisnis dan Manajemen, 2026)
This study aims to examine the role of customer satisfaction in mediating the influence of service quality and trust on customer loyalty among customers of PT Mega Central Finance (MCF) Garut Branch. This study applies a quantitative approach with descriptive method and causal associative method. Data collection was carried out through distributing questionnaires using a five-point Likert scale involving 100 respondents determined through a purposive sampling approach, with the consideration that they meet the characteristics that suit the needs of the study. Data were analyzed using a Structural Equation Modeling (SEM) model based on Partial Least Squares (PLS-SEM) on SmartPLS 3 software assistance. The findings of this study indicate that service quality has a positive and significant effect on customer loyalty; trust has a positive and significant effect on customer loyalty; service quality has a positive and significant effect on customer satisfaction; trust has a positive and significant effect on customer satisfaction; and customer satisfaction has a positive and significant effect on customer loyalty. Based on the results of the mediation test, customer satisfaction mediates the effect of service quality on customer loyalty positively and significantly, and customer satisfaction mediates the effect of trust on customer loyalty positively and significantly. The practical implication of this research is that PT MCF Garut Branch needs to prioritize improving service quality in the responsiveness dimension and trust in the competence dimension to build satisfaction that has an impact on customer loyalty.